The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/nano12152677
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Methylene Blue Photodegradation Rate Using Laser Synthesized Ag-Doped ZnO Nanoparticles

Abstract: In this work, Ag-doped ZnO nanoparticles are obtained via pulsed laser ablation of the Ag-coated ZnO target in water. The ratio of Ag dopant in ZnO nanoparticles strongly depends on the thickness of the Ag layer at the ZnO target. Synthesized nanoparticles were characterized by XRD, XPS, SEM, EDS, ICP-OES, and UV–VIS spectrophotometry to obtain their crystal structure, elemental composition, morphology and size distribution, mass concentration, and optical properties, respectively. The photocatalytic studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Fitting the Ag 3d fine spectrum shows two peaks centered at 367.5 and 373.5 eV corresponding to Ag 3d 5/2 and Ag 3d 3/2 , respectively. Compared to the pure Ag films (Ag 3d 5/2 , 368.2 eV and Ag 3d 3/2 , 374.2 eV), the shift in binding energy is associated with the electron transfer between Ag particles and ZnO films . The O 1s fine spectrum in Figure d is well reproduced by two Lorentzian–Gaussian peaks situated at 530.42 and 531.89 eV, which is correlated with oxygen in the ZnO crystal lattice and surface-chemical-absorbed O 2 , respectively …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Fitting the Ag 3d fine spectrum shows two peaks centered at 367.5 and 373.5 eV corresponding to Ag 3d 5/2 and Ag 3d 3/2 , respectively. Compared to the pure Ag films (Ag 3d 5/2 , 368.2 eV and Ag 3d 3/2 , 374.2 eV), the shift in binding energy is associated with the electron transfer between Ag particles and ZnO films . The O 1s fine spectrum in Figure d is well reproduced by two Lorentzian–Gaussian peaks situated at 530.42 and 531.89 eV, which is correlated with oxygen in the ZnO crystal lattice and surface-chemical-absorbed O 2 , respectively …”
Section: Resultsmentioning
confidence: 90%
“…The Zn 2p 3/2 and 2p 1/2 peaks are situated at approximately 1021.5 and 1044.7 eV, respectively, and the standard energy difference of 23 eV indicates that the Zn element exists in the form of Zn 2+ , which also confirms the existence of ZnO. 22 Figure 4c shows the binding energy of the Ag 3d peak. Fitting the Ag 3d fine spectrum shows two peaks centered at 367.5 and 373.5 eV corresponding to Ag 3d 5/2 and Ag 3d 3/2 , respectively.…”
Section: Characterization Of Ag-loaded Znomentioning
confidence: 85%
“…Generally, in UV-vis spectroscopy, this can result in a decrease in absorbance at the wavelength of interest. However, in some cases [22][23][24][25], photobleaching can also cause an increase in absorbance, because of the formation of a new product from the photobleaching of MB or a shift in the absorbance spectrum, resulting in a higher absorbance at 664 nm. It would be interesting to investigate this further in a subsequent investigation.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…Moreover, many reported studies have shown that ZnO modified with appropriate dopants (such as rare-Earth (RE) elements and noble metals) can exhibit improved properties compared to the pristine ZnO in different applications [8][9][10][11][12][13][14][15]. For example, the photocatalytic properties of ZnO nanoparticles have been enhanced upon doping with europium ions (Eu 3+ ) [16][17][18], erbium ions (Er 3+ ) [19][20][21][22][23][24][25], and by hybridization with selected noble metal such as silver (Ag) [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The observed effective separation of the photo-generated charges in ZnO has been attributed to the electron-scavenger effect of the noble metal [26] and the point defects introduced by RE-doping [23].…”
Section: Introductionmentioning
confidence: 99%
“…Also, ZnO NPs with antibacterial activity [53], and Zn@ZnO core-shell nanostructures for sensing hydroquinone [54] have been synthesized by PLAL. In addition, Ag/ZnO nanoparticles with enhanced photocatalytic activity [36,55] and anticancer nature [56], have been produced by PLAL using Zn and Ag metallic targets [55,56] and Ag-coated ZnO target [36] in water. Furthermore, Ag/Au-ZnO plasmonic hybrid nanomaterials have been synthesized by pulsed laser ablation of Ag/Au bimetallic in water followed by mixing with ZnO nano-powder and by laser irradiation of the mixture [57].…”
Section: Introductionmentioning
confidence: 99%